5(1+5k)-3=-29-6k

Simple and best practice solution for 5(1+5k)-3=-29-6k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(1+5k)-3=-29-6k equation:


Simplifying
5(1 + 5k) + -3 = -29 + -6k
(1 * 5 + 5k * 5) + -3 = -29 + -6k
(5 + 25k) + -3 = -29 + -6k

Reorder the terms:
5 + -3 + 25k = -29 + -6k

Combine like terms: 5 + -3 = 2
2 + 25k = -29 + -6k

Solving
2 + 25k = -29 + -6k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '6k' to each side of the equation.
2 + 25k + 6k = -29 + -6k + 6k

Combine like terms: 25k + 6k = 31k
2 + 31k = -29 + -6k + 6k

Combine like terms: -6k + 6k = 0
2 + 31k = -29 + 0
2 + 31k = -29

Add '-2' to each side of the equation.
2 + -2 + 31k = -29 + -2

Combine like terms: 2 + -2 = 0
0 + 31k = -29 + -2
31k = -29 + -2

Combine like terms: -29 + -2 = -31
31k = -31

Divide each side by '31'.
k = -1

Simplifying
k = -1

See similar equations:

| 28w-3=5w-0.8 | | 12-5x+2x=-8x+37 | | -5+n=1 | | x-37=48 | | (y-4)*2+(y+1)*2=(y-2)*2+(y+6)+3 | | 1.4d=1.4d+9.21 | | (-61)+x=-60 | | 39-6v=-v-4(8v-3) | | -12=10(u-2) | | m^2-2m-21=0 | | 22y=7(3x-6) | | 15/-20 | | -7.17-17.8k=-17.8k-7.17 | | 62+x=84 | | 12.2t+5.93=5.93+12.2t | | -5(x+2)-11=15+4 | | (-96)+x=-55 | | -3j^2+12j+21=0 | | 36-2x=-8(5x+5) | | -12=3(u-2) | | 3x+2(3x-4)=-53 | | -2.04+13.9f+11.87=-1.75+13.9f | | 1/3x-1/2=5 | | 12/4=r/6 | | x-61=30 | | 47+x=-66 | | 8+5r-3=9r+6-3r | | -20c-13=-2-20c-11 | | 24=90n | | 7(6+5n)-7n=-8n+6 | | -3q^2+6q=-123 | | 9x-(4x+6)=2(2x+1) |

Equations solver categories